The Most Important Thing That Ever Happened: Big, Bad Data and the Doubling of Human Life Expectancy. (February 2022) - Berry, Stephen
The global doubling of human life expectancy between 1850 and 1950 is arguably the most important thing that ever happened, undergirding massive improvements in human life and lifestyles while also contributing to insectageddons, septic oceans, and collapsing ecosystems. The story of that global doubling is typically told as a series of medical breakthroughs—Jenner and vaccination, Lister and antisepsis, Snow and germ theory, and Fleming and penicillin—but the lion's share of the credit belongs to urban planning based upon good data. Until we had sophisticated systems of death registration, we could not conceive of the health problems we were facing, much less solve them. Today, the greatest threat we face is not disease but data denial.